SILENCIAMENTO E MEMORIA: DISCURSO E COLONIZACAO BRITANICA NA INDIA - Grigoletto, Marisa (Organon, 2003)
This paper aims at analysing a specific way in which memoryand silence function in the discourse of the coloniser in a colonial settingso as to comprehend the conflicts and “slippages” of meaning in a mannerof representing both the colonial relationship and the colonised subject.An investigation of British political discourse about India in the fewyears that preceded the transfer of power to India and during which theconcession of independence was prepared will yield an analysis and adiscussion of meanings of pre-independence discourse that are closelyrelated to the memory of a colonialist discursive formation of a dominantpower in disguise and of the conflicting relationship between the recognitionof a full-fledged political subject position that is silenced for thecoloniser and prevented from being imprinted in the memory of theenunciative event and nevertheless its reinscription in the same enunciativeevent.